A study of the effect of radiation on the mechanical strength of optical fibres - Arvidsson, B; Cindro, V; Huffman, B; Issever, C; Teng, P; Weidberg, A; Wilson, J (2013)
The fibres used for the readout of the upgraded LHC detectors for the High Luminosity Large Hadron Collider (HL-LHC) will be exposed to very high radiation doses of up to ∼ 500 kGy(Si). This study has focused on the mechanical reliability of optical fibres after radiation to the levels expected at HL-LHC. Multimode and single-mode fibres from two manufacturers were tested. © 2013 IOP Publishing Ltd and Sissa Medialab srl.